2017
DOI: 10.1111/apt.13972
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the impact of Clostridium difficile infection on the short‐ and long‐term risks of colectomy in inflammatory bowel disease

Abstract: Based on 12 observational studies with at least moderate quality, Clostridium difficile infection appears to increase colectomy risk in IBD in the long- but not short- term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Diagnosing and treating CDI in the IBD population is challenging due to the similar clinical and endoscopic presentations of IBD flare and CDI. [ 38 ] Current evidence indicates that CDI in IBD patients is associated with worse outcomes, as reflected by the need for colectomy, [ 39 , 40 ] escalation of treatment, recurrent hospitalizations, [ 15 ] a prominent increase in recurrent infection rates, [ 41 43 ] and a higher mortality rate, [ 33 , 44 ] all of which warrant further evaluation of the prevalence, potential risk factors, and impact of CDI on IBD patients’ outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing and treating CDI in the IBD population is challenging due to the similar clinical and endoscopic presentations of IBD flare and CDI. [ 38 ] Current evidence indicates that CDI in IBD patients is associated with worse outcomes, as reflected by the need for colectomy, [ 39 , 40 ] escalation of treatment, recurrent hospitalizations, [ 15 ] a prominent increase in recurrent infection rates, [ 41 43 ] and a higher mortality rate, [ 33 , 44 ] all of which warrant further evaluation of the prevalence, potential risk factors, and impact of CDI on IBD patients’ outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of 12 observational studies reported that CDI appears to increase long-term colectomy risk in patients with UC (odds ratio, 2.96; 95% CI, 1.19-7.34). 28 Here, we demonstrated that CDI was one of the significant predictors of colectomy in the overall study cohort with ASUC (HR, 4.61; 95% CI, 1.50-14.23). Our findings bolster the relevant clinical implication that CDI should be more aggressively screened for and managed in hospitalized patients with ASUC, particularly when considering IFX therapy.…”
Section: Discussionmentioning
confidence: 60%
“…CDI is extremely common in the elderly and immunocompromised patients such as cancer and IBD patients who develop CDI and leads to adverse outcomes in these patients compared to the general population . FMT has been successful for recurrent CDI not only in otherwise healthy adults, but also in patients who are elderly and have comorbid conditions or are immunosuppressed.…”
Section: Microbiota Replacement Therapies For CDImentioning
confidence: 99%